The Effectiveness of the Islamic Boarding School Diniyah Program on Students’ Achievement in Fiqh at Madrasah Aliyah Nurul Yaqin, Sorong Regency - Ana Tri Mahmudah; Intan Febrianti; Achmad Fatwa; Fitria Nursitasari; Abdul Aziz Khoiri (IQRO: Journal of Islamic Education, 2026)
This study examines the implementation of the diniyah program at Nurul Yaqin Islamic Boarding School, Sorong Regency, and its effectiveness in supporting students’ achievement in Fiqh at Madrasah Aliyah Nurul Yaqin. The study was motivated by the presence of two groups of students within the same madrasah environment: boarding students who lived in the pesantren and participated in the diniyah program, and non-boarding students who did not participate in it. This study employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving the school principal, the Fiqh teacher, a diniyah coordinator, and boarding students. The findings show that the diniyah program was implemented in four daily sessions after the Ashar, Maghrib, Isha, and Fajr prayers. The program used classical Islamic texts such as Safinatun Najah, Taqrib, and Fath al-Qarib, and employed sorogan, bandongan, memorization, and collective study methods. Students who joined the diniyah program demonstrated stronger conceptual understanding, greater classroom readiness, higher confidence, and more active participation in Fiqh lessons than students who did not join the program. Documentation of learning outcomes also indicates a higher average Fiqh score among diniyah participants. In addition to strengthening academic achievement, the program fostered discipline, religious practice, and learning motivation. The study concludes that the diniyah program was effective in supporting Fiqh learning achievement at Madrasah Aliyah Nurul Yaqin, although its implementation also required careful management of student workload and rest time.